The first order and second order linear difference equations and its applications - 493007 Nur Syahirah Shamsuddin; Mohd. Nor Mohamad; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2009